NILAI-NILAI MORAL PADA FILM THEEB KARYA NAJI ABU NOWAR KAJIAN SEMIOTIKA CHARLES SANDERS PIERCE - Alfina Hartono Putri; Dede Sasa Nurjaman; Rohanda Rohanda (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research aims to describe the moral values in the movie Theeb by Naji Abu Nowar, which is set in World War I in the Middle East, during the Arab uprising against the Ottoman Empire. Arab revolt against the Ottoman Empire. The movie uses non-professional actors from the Bedouin community in southern Jordan. The story centers on Theeb, a young boy struggling to survive in the desert after his older brother Hussein after his older brother, Hussein, was shot dead by a tribe that was after their camel while traveling with British soldiers. while traveling with British soldiers. In this event, there are many moral values that can be learned. This research is a qualitative descriptive study this study is a qualitative descriptive study with the object of cut scenes in the movie. Analysis is done by classifying signs based on representamen, object, and interpretant. The results show various moral values such as knowledge, beliefs, arts, morals, laws, customs, abilities, and habits.